MOTIF BATIK DI RUMAH BATIK SAMPAN PESONA MINANG DI DESA SUNGAI KASAI PARIAMAN SELATAN - Ramadhani Zuhuri; Ezriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the batik motifs found at Sampan Pesona Minang Batik House in Sungai Kasai Village, South Pariaman, and to explain the sources of inspiration behind their creation in relation to local culture. This research employed a descriptive qualitative method using observation, interviews, documentation, and literature review for data collection. The findings reveal that the batik house has five main motifs: Tabuik Salingka Bungo Paku, Sampan, Tabuik Sala, Tabuik Balago, and Kabau Padati, all of which are stylized representations of the cultural heritage and daily life of the Pariaman and Minangkabau communities. The motifs are inspired by the Tabuik tradition, coastal life, regional culinary heritage, and agrarian culture, and are transformed into decorative designs while preserving their original identity. In addition to their aesthetic value, these motifs embody symbolic meanings that represent cultural identity, togetherness, mutual cooperation, perseverance, and the relationship between humans and nature. Therefore, the batik motifs of Sampan Pesona Minang Batik House serve as a form of local cultural preservation while strengthening the identity of regional batik as part of culture-based creative industry development.